Respiratory function in healthy Emirati children using forced oscillations - Alblooshi, A.; Alkalbani, A.; Narchi, H.; Al-Hamad, S.; Al-Houqani, M.; Albadi, G.; Souid, A.; Hall, Graham (Wiley-Liss, Inc, 2018)
© 2018 Wiley Periodicals, Inc. Background: The forced oscillation technique (FOT) allows the quantification of respiratory function, does not require active cooperation and as such is ideally suited for use in young children. The application of the FOT in non-Caucasian populations is limited and it remains unclear if current reference ranges for the FOT in Caucasian children are appropriate for children in the Arabian Peninsula. This study explored the use of the FOT in healthy school-aged children in the United Arab Emirates (UAE). Methods: Lung function using FOT was assessed in healthy Emirati children aged 4-12 years. Using a validated questionnaires general medical and respiratory histories were obtained. Prediction equations for resistance (Rrs), reactance (Xrs), and area under reactance curve (AX) were calculated and compared to previous studies. Results: FOT was successfully obtained in 291 healthy Emirati children. Linear regression modelling including weight, height, age, and gender in transformed FOT outcomes demonstrated that height was the strongest predictor of FOT outcomes (P < 0.001). Using the equated prediction equation Z-scores were calculated. FOT outcomes in Emirati children did not match previously published reference equations in Caucasians children (P < 0.001). Conclusion: FOT measurements were feasible in Emirati school-children. New FOT reference equation in Emirati children were derived. FOT reference equation in Emirati children was different from published equations in Caucasians.